PENDAMPINGAN BELAJAR ILMU TAJWID UNTUK MENINGKATKAN KEMAMPUAN BACA AL QUR’AN SISWA TPA DI DUKUH WATU AGUNG DESA DAYAKAN KECAMATAN BADEGAN PONOROGO - Anjelina (Journal of Islamic Science Community, 2022)
Watu Agung Hamlet, Dayakan Village is one of the remote areas in the Ponorogo district. The community service program carried out at TPA Sabilul Huda Dukuh Watu Agung aims to: (1) improve students' ability to read the Qur'an, (2) teach the science of Tajwid to students (3) as a form of team concern in implementing community service programs. The method used is mentoring through direct observation and face-to-face activities. The results of the mentoring showed that students' interest in reading the Qur'an increased with the mentoring activities for learning Tajweed, as evidenced by their enthusiasm in responding to learning during the mentoring process. The implementation of this PKM is running effectively. In addition, there is an increase in students' ability to read the Qur'an with Tajweed.